If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -5 = 1 Reorder the terms: -5 + 3g = 1 Solving -5 + 3g = 1 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3g = 1 + 5 Combine like terms: -5 + 5 = 0 0 + 3g = 1 + 5 3g = 1 + 5 Combine like terms: 1 + 5 = 6 3g = 6 Divide each side by '3'. g = 2 Simplifying g = 2
| x-14+2x=16 | | (2y-1)(y-2)=6 | | 9x+84=12 | | 5y+13=2y+22 | | 6x-4-4x=2x-4 | | 4x+15=24 | | 24-64n=-8(-3+8n) | | 7x-13=42 | | 4x^2-17x-15=30 | | -85=5(2n-3) | | 3x+10=2x-x+18 | | 11x+25=78 | | -2(z-3)-4=18 | | -2-(12x+8)+17=3+x-(13x-4) | | -12z-29=5(z+6)-195 | | 5(v-8)-2=5v+29 | | a(t)=t^2-6t+24 | | 1.6+0.2x=0.4x-3.2 | | 60x^2+300x=0 | | 12+v=-9 | | 12x-18=53 | | (3x-x)(x+3.464)=0 | | 6m-19=-2(-3m+8) | | 3x+27=102 | | 12(4-6x)+8=5 | | k+12=-9 | | 13x-4=17x+4 | | 3a^2-27a^2b=0 | | 25=y+19 | | 18-(9-5x)x=4 | | 3(y+4)=33 | | 678=789 |